A note on biological data from the hunt of bowhead whales in West Greenland 2009–2011 - Heide-Jørgensen, M. P.; Garde, E.; Nielsen, N. H.; Andersen, O. N.; Hansen, S. H. (J. Cetacean Res. Manage., 2023)
One male and six female bowhead whales were taken for subsistence in Disko Bay, West Greenland, in April–May 2009–2011. All of these whales were sexually mature with body lengths exceeding 14m. One female was pregnant with a 3.87m foetus and three others presumably had small foetuses that were not detected in the field. Another female that showed no signs of recent pregnancy had a minimum of 7–8 corpora albicantia but no mature follicles. One 14.10m male with a 42kg testis was classified as sexually mature. Estimated ages of the whales were between 37 and 50 yrs. The observations on growth and reproduction were consistent with data on bowhead whales in Alaska. Four of the whales had recently been feeding as their stomachs contained calanoid copepods, especially Calanus hyperboreus.